(untitled) (Scientia Agricola, 2011)
Legumes as green manure are alternative sources of nitrogen (N) for crops and can supplement or even replace mineral nitrogen fertilization due to their potential for biological nitrogen fixation (BNF). The utilization of nitrogen by sugarcane (Saccharum spp.) fertilized with sunn hemp (Crotalaria juncea L.) and ammonium sulfate (AS) was evaluated using the 15N tracer technique. N was added at the rate of 196 and 70 kg ha-1 as 15Nlabeled sunn hemp green manure (SH) and as ammonium sulfate (AS), respectively. Treatments were: (i) Control; (ii) AS15N; (iii) SH15N + AS; (iv) SH15N; and (v) AS15N + SH. Sugarcane was cultivated for five years and was harvested three times. 15N recovery was evaluated in the two first harvests. In the sum of the three harvests, the highest stalk yields were obtained with a combination of green manure and inorganic N fertilizer; however, in the second cutting the yields were higher where SH was used than in plots with AS. The recovery of N by the first two consecutive harvests accounted for 19 to 21% of the N applied as leguminous green manure and 46 to 49% of the N applied as AS. The amounts of inorganic N, derived from both N sources, present in the 0-0.4 m layer of soil in the first season after N application and were below 1 kg ha-1.